Automatic controller bathroom light and fans / Dino Amsyar Salehan & Muhamad Harith Hasbullah - Salehan, Dino Amsyar; Hasbullah, Muhamad Harith (2015)
A light and fan on the toilet is being automated from manual for some advantage. It can reduce the usage of electricity. For automatic ON and OFF light, LDR is use to detect the intensity of light. If the intensity is high the light will turn OFF. For automatic ON and OFF fans, it will operate using synchronous motor and used AC power supply for long term. It will keep bathroom smell fresh when want to used it. The overall, this final report is established to fulfill the diploma project requirement for final semester student, a standard guideline is prepared to standardize various documentations and this report is done mainly to list down all the important aspect of the project that have been designed.